LEXICAL REITERATION IN EFL YOUNG LEARNERS’ ESSAYS: DOES IT RELATE TO THE TYPE OF INSTRUCTION? - Agustín Llach, Mª Pilar; Jiménez Catalán, Rosa Mª (International Journal of English Studies, 2009)
The purpose of this study is to ascertain whether the type of instruction (English as vehicular language and English as a subject) is related to the use of reiteration ties. In the first place, we identified, classified, and counted the number and kind of reiteration ties used by two groups of EFL learners. Secondly, we examined whether reiteration as a mechanism of lexical cohesion correlates with learners’ language level. Thirdly, we looked at students data in order to determine if lexical reiteration is associated with lexical variation. Results point to a similar pattern for both groups with regard to the use of reiteration ties: content and non-content students resort to word repetition rather than to other devices of lexical reiteration. Differences were found in favour of content students concerning lexical variation, language level, and use of antonyms and general nouns.